2011
DOI: 10.1177/2153368710383869
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Analysis of Race on the Decision to Petition a Case in the Juvenile Court

Abstract: There is a large body of research examining the impact of race on juvenile court outcomes. Fewer studies have specifically examined the decision by prosecutors to formally petition a case to the juvenile court. A much smaller body of literature statistically controls for structural level variables (e.g., population density and racial composition), while examining the impact of race. Using the symbolic threat hypothesis, the current study examines the effect of race on the decision to petition a case to the juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 29 publications
(64 reference statements)
3
54
0
Order By: Relevance
“…Focusing on the petition decision, Freiburger and Jordan (2011) used offense-level data from all youth processed for misdemeanor and felony offenses in the juvenile court system in West Virginia during the year 2005 and found that offenses were more likely to be petitioned to juvenile court in counties with higher rates of poverty and lower proportions of female-headed households. Cross-level findings indicated that the effects of racial group and county-level poverty significantly interacted such that Black youth had the highest likelihood of petition in counties with greater levels of poverty.…”
mentioning
confidence: 99%
“…Focusing on the petition decision, Freiburger and Jordan (2011) used offense-level data from all youth processed for misdemeanor and felony offenses in the juvenile court system in West Virginia during the year 2005 and found that offenses were more likely to be petitioned to juvenile court in counties with higher rates of poverty and lower proportions of female-headed households. Cross-level findings indicated that the effects of racial group and county-level poverty significantly interacted such that Black youth had the highest likelihood of petition in counties with greater levels of poverty.…”
mentioning
confidence: 99%
“…As such, the studies which we review regarding geographic disparities all analyze units of geography smaller than municipalities. We do not address literature on geographic disparities in juvenile justice contact at other levels, such as between counties (e.g., Freiburger & Jordan, 2011;Leiber, Peck, & Rodriguez, 2016;Lowery, Burrow, & Kaminski, 2018;Thomas, Moak, & Walker, 2013).…”
mentioning
confidence: 99%
“…Moreover, they represent the more than 70% of youth who are involved in school-related arrests and are more likely to be sentenced as adults, in spite of state and federal legislation to produce more equitable treatment in courts (Brinkley-Rubenstien, Craven & McCormack, 2014; Mendel, 2011; Rodriguez, 2010; Rodriguez, 2007; United States Department of Education, 2012). Consequently, scholars suggest that these disparities are the result of blatant bias or racial discrimination based on social and structural factors (e.g., poverty, population density, female-headed households, racial composition, residential mobility) or legal factors (e.g., penalties for drug crimes, or the aforementioned unfair sentencing practices) and play a significant role for Black versus White youth (Brinkley-Rubinstein, Craven, & McCormack, 2014; Case, 2008; Freiburger & Jordan, 2011; Mitchell & Caudy, 2015; Sampson & Loeffler, 2010). However, more research is needed to disentangle the complex associations among systems involvement, academic outcomes, and the presence of organizational, systemic, and intersectional structural factors impacting Black youth.…”
Section: Discussionmentioning
confidence: 99%